2013
DOI: 10.1111/bph.12194
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induces insulin secretion by direct activation of L‐type calcium channels in pancreatic beta cells

Abstract: BACKGROUND AND PURPOSEQuercetin is a natural polyphenolic flavonoid that displays anti-diabetic properties in vivo. Its mechanism of action on insulin-secreting beta cells is poorly documented. In this work, we have analysed the effects of quercetin both on insulin secretion and on the intracellular calcium concentration ([Ca 2+ ]i) in beta cells, in the absence of any co-stimulating factor. EXPERIMENTAL APPROACHExperiments were performed on both INS-1 cell line and rat isolated pancreatic islets. Insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 43 publications
9
69
1
3
Order By: Relevance
“…Quercetin caused significant depletion of cytosolic calcium levels and decreased calcium uptake from the intracellular stores in MDA MB 231 cells [24]. Quercetin could stimulate insulin secretion by increasing Ca 2+ influx through an interaction with L-type Ca 2+ channels [25]. Natsume et al [26] reported that quercetin suppressed the ER stress caused by calcium dynamics dysregulation by the inhibition of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin caused significant depletion of cytosolic calcium levels and decreased calcium uptake from the intracellular stores in MDA MB 231 cells [24]. Quercetin could stimulate insulin secretion by increasing Ca 2+ influx through an interaction with L-type Ca 2+ channels [25]. Natsume et al [26] reported that quercetin suppressed the ER stress caused by calcium dynamics dysregulation by the inhibition of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin interacts with L-type Cav1 in a different site from that of the agonist Bay K 8644 (1,phenyl]-3-pyridinecarboxylic acid, methyl ester). The mechanism acts by shifting the voltage-dependent activation toward negative potentials (Bardy et al, 2013). L-type Cav1 channels are the major contributors to the whole cell Cav current and insulin granule exocytosis in human, rat, and mouse beta cells.…”
Section: Pharmacology Of Cav Channels In Pancreatic Beta Cellsmentioning
confidence: 99%
“…Quercetin has a variety of activities in man. For example, it has been reported to have antioxidant [5][6][7], anti-inflammatory [8], anti-anaphylactic [9], anti-aging [10], antiplatelet aggregatory [11], radioprotective [12], immunomodulatory [13], antidiabetic [14], and anticancer [15] effects, and to improve lipid metabolism [16,17] and endurance exercise capacity [18]. Quercetin also reduces gastrointestinal (GI) intestinal transit in mice [19], induces intestinal smooth muscle relaxation [20], and prevents castor oil-induced diarrhea [21].…”
Section: Introductionmentioning
confidence: 99%